Practices of decision making in priority setting and resource allocation: A scoping review and narrative synthesis of existing frameworks - Brayan V. Seixas; François Dionne; Craig Mitton (Health Economics Review, 2021)
Background: Due to growing expenditures, health systems have been pushed to improve decision-making practices on resource allocation. This study aimed to identify which practices of priority setting and resource allocation (PSRA) have been used in healthcare systems of high-income countries. Methods: A scoping literature review (2007-2019) was conducted to map empirical PSRA activities. A two-stage screening process was utilized to identify existing approaches and cluster similar frameworks. That was complemented with a gray literature and horizontal scanning. A narrative synthesis was carried out to make sense of the existing literature and current state of PSRA practices in healthcare. Results: One thousand five hundred eighty five references were found in the peer-reviewed literature and 25 papers were selected for full-review. We identified three major types of decision-making framework in PSRA: 1) Program Budgeting and Marginal Analysis (PBMA); 2) Health Technology Assessment (HTA); and 3) Multiple-criteria value assessment. Our narrative synthesis indicates these formal frameworks of priority setting and resource allocation have been mostly implemented in episodic exercises with poor follow-up and evaluation. There seems to be growing interest for explicit robust rationales and ample stakeholder involvement, but that has not been the norm in the process of allocating resources within healthcare systems of high-income countries. Conclusions: No single dominate framework for PSRA appeared as the preferred approach across jurisdictions, but common elements exist both in terms of process and structure. Decision-makers worldwide can draw on our work in designing and implementing PSRA processes in their contexts.
Keywords: 330; Priority setting; Resource allocation; Frameworks; Health economics; Efficiency